KEPUASAN KERJA DAN MOTIVASI KERJA PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN AKPER SAIFUDDIN ZUHRI INDRAMAYU 2019: KEPUASAN KERJA DAN MOTIVASI KERJA PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN AKPER SAIFUDDIN ZUHRI INDRAMAYU 2019 - Ani Kuspini (Universitas Widyatama, 2020)
In this global era, business competition between companies is very tight, including in the field of education. Serving in this field needs special attention, because it is about student satisfaction, so it requires employees who have moral, professional, discipline and responsibility in carrying out their duties. This is necessary to increase work productivity, serve quality, and strengthen competition in our own country and abroad. However, in fact, there are still employees whose work productivity is lacking. Some literature says that work productivity is also influenced by job satisfaction and motivation. Based on the above background, in this study the writer chose Saifuddin Zuhri nurse academy as the research object.The total number of employees is twenty one consisting of leaders and workers selected as the sample set as the total sampling. The purpose of this study was to determine the effect of job satisfaction and work motivation factors on the work productivity of employees of the nurse academy, Saifuddin Zuhri Indramayu. From the research it can be concluded that the validity and reliability tests of all respondents have met the requirements. From the partial test, the variables of satisfaction and work motivation have a significant effect on work productivity. and based on the regression equation shows that the work motivation variable has a greater influence on work productivity. The joint test of the two variables also has a significant effect, and the coefficient of determination of the two variables, job satisfaction and motivation, can explain the work productivity variables.